MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA ANIMASI PADA PESERTA DIDIK KELAS 1 SD MUHAMMADIYAH 2 LIMBOTO KABUPATEN GORONTALO - Dewi Ahmad; Irmawati Duko Ishak; Fandi H. Binggo (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2025)
The purpose of this study is to improve the beginning reading skills of first-grade students at SD Muhammadiyah 2 Limboto, Gorontalo Regency, through the use of animated media. The type of research used is classroom action research, with the research subjects being 19 first-grade students of SD Muhammadiyah 2 Limboto. The research employed observation, tests, and documentation techniques. The data analysis techniques included data on teacher activities, student activities, and students’ beginning reading skills. The results of the study showed that in the initial observation, 7 students (37%) were able to read at the beginning level. In the first cycle, 13 students (68%) demonstrated the ability, while in the second cycle, 18 students (95%) were able to read at the beginning level. Thus, it can be concluded that animated media can improve the beginning reading skills of first-grade students at SD Muhammadiyah 2 Limboto, Gorontalo Regency.